A new Cephennium of Kyrgyzstan, with notes on subgenera and distribution (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł; Stevanović, Miroslav (Zootaxa, 2015)
Cephennium chirgisianum sp. n. of western Kyrgyzstan is described. This is the easternmost known locality where this predominantly western European genus occurs. This new species is not placed in any subgenus, and problems with subgeneric diagnoses and systematics of Cephennium are discussed. The distribution of Cephennium is summarized and possible dispersal routes or areas where this genus can be expected to occur are indicated.